2006
DOI: 10.1590/s1519-566x2006000400001
|View full text |Cite
|
Sign up to set email alerts
|

Invasions by Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) in the Western Hemisphere: implications for South America

Abstract: Invasões de Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) no Hemisfério Ocidental: Implicacões para a América do Sul RESUMO -A joaninha, Harmonia axyridis (Pallas), nativa da Ásia, foi recentemente detectada na América do Sul depois de ter invadido a América do Norte e Europa. Essa joaninha é um predador voraz, e portanto, popular e eficaz no controle biológico. Infelizmente, H. axyridis também está relacionada a impactos nocivos (ex., como peste residencial e de frutas temperadas e ameaça a organismo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
150
1
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(158 citation statements)
references
References 62 publications
2
150
1
5
Order By: Relevance
“…A striking example of a deliberate introduction that has gone out of control is that of the multicolored Asian ladybird Harmonia axyridis (Pallas, 1773) (Coleoptera, Coccinellidae). H. axyridis is native to Asia between Siberia at the North and Southern China at the South, and from the Altai Mountains to the Pacific Ocean including Korea and Japan [3]. It was first introduced in North America in 1916 for biological control of agricultural pests such as aphids and scale insects on crops including citrus, maize, and tobacco [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A striking example of a deliberate introduction that has gone out of control is that of the multicolored Asian ladybird Harmonia axyridis (Pallas, 1773) (Coleoptera, Coccinellidae). H. axyridis is native to Asia between Siberia at the North and Southern China at the South, and from the Altai Mountains to the Pacific Ocean including Korea and Japan [3]. It was first introduced in North America in 1916 for biological control of agricultural pests such as aphids and scale insects on crops including citrus, maize, and tobacco [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…We collected host range data from the literature (e.g. Koch et al 2006;Loomans, unpublished) and found that H. axyridis may feed on many aphid species, as well as on numerous other insect prey (e.g. Hemiptera, Psyllidae, Coccoidea, Chrysomelidae, Curculionidae, Coccinellidae and Lepidoptera), spider mites (Tetranychidae), dead insects and also on plant material (e.g.…”
Section: Risk Identification and Risk Index For H Axyridis Based On mentioning
confidence: 99%
“…The species attacks many non-target organisms including beneficial insects and insects of conservation concern (Ware and Majerus 2007), has resulted in the reduction of populations of native predators in North America, is known as a nuisance in North America and recently also in Northwest Europe, and is a pest of fruit production in North America (e.g. Koch et al 2006 and references therein). The estimate for likelihood of effects on non-target populations is ''very likely''.…”
Section: Risk Identification and Risk Index For H Axyridis Based On mentioning
confidence: 99%
See 1 more Smart Citation
“…Many attempts to introduce MALB into North America have taken place since 1916, though it apparently did not establish until 1988 (Koch 2003 ) . It has since spread to South America and Europe (Koch et al 2006 ) . The multicolored Asian lady beetle is now an important contributor to biological control.…”
Section: Introductionmentioning
confidence: 99%